Enhancing Assertiveness through Self-Esteem Development: A Study of Indonesian Language Learning in Elementary Schools - Doni Nur Hamzah; Syaiful Bahri; Asmoni Asmoni (AL-ISHLAH: Jurnal Pendidikan, 2025)
Elementary school students often struggle to express their opinions assertively without offending others, indicating weak assertive behavior. This may be influenced by their self-esteem. Understanding this relationship is essential, particularly within the context of Indonesian language learning, where communication skills are central. This study employed a quantitative, correlational design to examine the relationship between self-esteem and assertive behavior among elementary students. A total of 30 fourth-grade students from a randomly selected elementary school in Sumenep Regency participated. Data were gathered using two questionnaires measuring self-esteem and assertive behavior, both utilizing a four-point Likert scale. The data were analyzed through linearity tests and simple linear regression. Findings revealed a positive, albeit statistically insignificant, relationship between self-esteem and assertive behavior (R² = 0.100; Sig. = 0.100). Self-esteem accounted for only 10% of the variance in assertive behavior. Despite the limited statistical significance, the trend aligns with theoretical assumptions that higher self-esteem may promote more assertive communication. While self-esteem appears to influence assertive behavior, it is not the sole contributing factor. The findings suggest that Indonesian language instruction has the potential to support affective development, but more comprehensive strategies are needed. Future research should explore additional variables and include larger, more diverse samples using a multivariate approach.